Childhood aggressive B‐cell non‐Hodgkin lymphoma in low–middle‐income countries. (6th December 2021) - Moleti, Maria Luisa; Testi, Anna Maria; Foà, Robin
Summary: In high‐income countries (HICs) paediatric aggressive B‐cell lymphomas are curable in about 90% of cases. Much worse results, with cure rates ranging from less than 30% to about 70%, are achieved in low‐ and middle‐income countries (LMICs), where 90% of paediatric non‐Hodgkin lymphomas occur. Low socio‐economic and cultural conditions, the lack of optimal diagnostic procedures, laboratory facilities and adequate supportive care exert a strong negative impact on compliance, treatment delivery, toxicity and, consequently, on the clinical outcome. Published data are scarce, generally originating from single institutions, and are difficult to compare. National and international cooperation projects have been undertaken to reduce the unacceptable gap between HICs and LMICs in the management of children with cancer, by promoting the sharing of knowledge and by implementing adequate local healthcare facilities, with initial promising results. In the present review, we will summarize the results so far obtained in the management of paediatric aggressive B‐cell NHL in LMICs.